(untitled) (International Journal of Engineering and Computer Science, 2017)
Orthogonal Frequency Division Multiplexing (OFDM) is used as a powerful multiplexing technique in wireless communication to avoid Frequency selective fading and better use of bandwidth efficiency. However, OFDM suffer from a major drawback at transmitter called Peak to Average Power Ratio (PAPR) of the transmitted OFDM signal . In order to overcome this drawback Selected Mapping (SLM) technique is commonly employed.It achieves PAPR reduction with increased computational complexity and side information requirements. In this work, modified SLM based on phase offset technique is proposed in MIMO-OFDM system. To compare the performance of proposed technique, conventional SLM (C-SLM)is considered. Results show that the proposed technique is more effective in reducing PAPR. In addition BER performance of the proposed technique is evaluated and presented.